Current Insights into Nonuniform Flow across Scales, Processes, and Applications - Najm, M.A. (2020)
This introduction to the special section Nonuniform Flow across Vadose Zone Scales is a brief summary of this special section's diverse contributions covering nonuniform flow across a wide range of scales, processes, and applications. We summarize the 17 articles constituting this special section and hope that those contributions are positive steps toward a new, generalizable, and comprehensive paradigm to modeling flow and transport in porous media.